A review of defect engineering, ion implantation, and nanofabrication using the helium ion microscope - Allen, Frances I. (Beilstein Journal of Nanotechnology, 2021)
The helium ion microscope has emerged as a multifaceted instrument enabling a broad range of applications beyond imaging in which the finely focused helium ion beam is used for a variety of defect engineering, ion implantation, and nanofabrication tasks. Operation of the ion source with neon has extended the reach of this technology even further. This paper reviews the materials modification research that has been enabled by the helium ion microscope since its commercialization in 2007, ranging from fundamental studies of beam–sample effects, to the prototyping of new devices with features in the sub-10 nm domain.
Keywords: defect engineering; focused helium ion beam-induced deposition; focused helium ion beam milling; helium ion beam lithography; helium ion implantation

(untitled) - Ward, B. W.; Notte, J. A.; Economou, N. P. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2006)

(untitled) - Morgan, J.; Notte, J.; Hill, R.; Ward, B. (Microsc. Today, 2006)

(untitled) - Notte, J.; Ward, B.; Economou, N.; Hill, R.; Percival, R.; Farkas, L.; McVey, S. (AIP Conf. Proc., 2007)

(untitled) - Bell, D. C. (Microsc. Microanal., 2009)

Springer Handbook of Microscopy - Hlawacek, G. (Ion Microscopy, 2019)

(untitled) - Joens, M. S.; Huynh, C.; Kasuboski, J. M.; Ferranti, D.; Sigal, Y. J.; Zeitvogel, F.; Obst, M.; Burkhardt, C. J.; Curran, K. P.; Chalasani, S. H.; Stern, L. A.; Goetze, B.; et al. (Sci. Rep., 2013)

(untitled) - Schmidt, M.; Byrne, J. M.; Maasilta, I. J. (Beilstein J. Nanotechnol., 2021)

(untitled) - Wirtz, T.; De Castro, O.; Audinot, J.-N.; Philipp, P. (Annu. Rev. Anal. Chem., 2019)

(untitled) - He, S.; Tian, R.; Wu, W.; Li, W.-D.; Wang, D. (Int. J. Extreme Manuf., 2021)

Helium Ion Microscopy - Hlawacek, G.; Gölzhäuser, A. (Springer International Publishing, 2016)

(untitled) - Stanford, M. G.; Lewis, B. B.; Mahady, K.; Fowlkes, J. D.; Rack, P. D. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2017)

(untitled) - Belianinov, A.; Burch, M. J.; Kim, S.; Tan, S.; Hlawacek, G.; Ovchinnikova, O. S. (MRS Bull., 2017)

Helium Ion Microscopy: Principles and Applications - Joy, D. C. (Springer, 2013)

Helium Ion Microscopy - Notte, J.; Huang, J. (The Helium Ion Microscope, 2016)

(untitled) - Tan, S.; Livengood, R.; Shima, D.; Notte, J.; McVey, S. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2010)

(untitled) - Livengood, R.; Tan, S.; Greenzweig, Y.; Notte, J.; McVey, S. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2009)

(untitled) - Livengood, R. H.; Tan, S.; Hallstein, R.; Notte, J.; McVey, S.; Faridur Rahman, F. H. M. (Nucl. Instrum. Methods Phys. Res., Sect. A, 2011)

(untitled) - Kretschmer, S.; Maslov, M.; Ghaderzadeh, S.; Ghorbani-Asl, M.; Hlawacek, G.; Krasheninnikov, A. V. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Nakaharai, S.; Iijima, T.; Ogawa, S.; Suzuki, S.; Li, S.-L.; Tsukagoshi, K.; Sato, S.; Yokoyama, N. (ACS Nano, 2013)

(untitled) - Moktadir, Z.; Hang, S.; Mizuta, H. (Carbon, 2015)

(untitled) - Zhou, Y.; Maguire, P.; Jadwiszczak, J.; Muruganathan, M.; Mizuta, H.; Zhang, H. (Nanotechnology, 2016)

(untitled) - Naitou, Y.; Ogawa, S. (AIP Adv., 2017)

(untitled) - Araujo, E. N. D.; Brant, J. C.; Archanjo, B. S.; Medeiros-Ribeiro, G.; Alves, E. S. (Phys. E (Amsterdam, Neth.), 2018)

(untitled) - Srivastava, S.; Kino, H.; Nakaharai, S.; Verveniotis, E.; Okawa, Y.; Ogawa, S.; Joachim, C.; Aono, M. (Nanotechnology, 2017)

(untitled) - Fox, D. S.; Zhou, Y.; Maguire, P.; O’Neill, A.; Ó’Coileáin, C.; Gatensby, R.; Glushenkov, A. M.; Tao, T.; Duesberg, G. S.; Shvets, I. V.; Abid, M.; Abid, M.; et al. (Nano Lett., 2015)

(untitled) - Stanford, M. G.; Pudasaini, P. R.; Gallmeier, E. T.; Cross, N.; Liang, L.; Oyedele, A.; Duscher, G.; MahjouriâSamani, M.; Wang, K.; Xiao, K.; Geohegan, D. B.; Belianinov, A.; et al. (Adv. Funct. Mater., 2017)

(untitled) - Jadwiszczak, J.; Keane, D.; Maguire, P.; Cullen, C. P.; Zhou, Y.; Song, H.; Downing, C.; Fox, D.; McEvoy, N.; Zhu, R.; Xu, J.; Duesberg, G. S.; et al. (ACS Nano, 2019)

(untitled) - Jadwiszczak, J.; Maguire, P.; Cullen, C. P.; Duesberg, G. S.; Zhang, H. (Beilstein J. Nanotechnol., 2020)

(untitled) - Stanford, M. G.; Pudasaini, P. R.; Belianinov, A.; Cross, N.; Noh, J. H.; Koehler, M. R.; Mandrus, D. G.; Duscher, G.; Rondinone, A. J.; Ivanov, I. N.; Ward, T. Z.; Rack, P. D. (Sci. Rep., 2016)

(untitled) - Iberi, V.; Liang, L.; Ievlev, A. V.; Stanford, M. G.; Lin, M.-W.; Li, X.; Mahjouri-Samani, M.; Jesse, S.; Sumpter, B. G.; Kalinin, S. V.; Joy, D. C.; Xiao, K.; et al. (Sci. Rep., 2016)

(untitled) - Cybart, S. A.; Cho, E. Y.; Wong, T. J.; Wehlin, B. H.; Ma, M. K.; Huynh, C.; Dynes, R. C. (Nat. Nanotechnol., 2015)

(untitled) - Sapozhnikov, M. V.; Petrov, Y. V.; Gusev, N. S.; Temiryazev, A. G.; Ermolaeva, O. L.; Mironov, V. L.; Udalov, O. G. (Materials, 2019)

(untitled) - Saremi, S.; Xu, R.; Allen, F. I.; Maher, J.; Agar, J. C.; Gao, R.; Hosemann, P.; Martin, L. W. (Phys. Rev. Mater., 2018)

(untitled) - Klein, J.; Lorke, M.; Florian, M.; Sigger, F.; Sigl, L.; Rey, S.; Wierzbowski, J.; Cerne, J.; Müller, K.; Mitterreiter, E.; Zimmermann, P.; Taniguchi, T.; et al. (Nat. Commun., 2019)

(untitled) - Choe, H. S.; Prabhakar, R.; Wehmeyer, G.; Allen, F. I.; Lee, W.; Jin, L.; Li, Y.; Yang, P.; Qiu, C.-W.; Dames, C.; Scott, M.; Minor, A.; et al. (Nano Lett., 2019)

(untitled) - Klein, J.; Kuc, A.; Nolinder, A.; Altzschner, M.; Wierzbowski, J.; Sigger, F.; Kreupl, F.; Finley, J. J.; Wurstbauer, U.; Holleitner, A. W.; Kaniber, M. (2D Mater., 2017)

(untitled) - Stanford, M. G.; Noh, J. H.; Mahady, K.; Ievlev, A. V.; Maksymovych, P.; Ovchinnikova, O. S.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Cho, E. Y.; Ma, M. K.; Huynh, C.; Pratt, K.; Paulson, D. N.; Glyantsev, V. N.; Dynes, R. C.; Cybart, S. A. (Appl. Phys. Lett., 2015)

(untitled) - Cho, E. Y.; Zhou, Y. W.; Cho, J. Y.; Cybart, S. A. (Appl. Phys. Lett., 2018)

(untitled) - Cho, E. Y.; Li, H.; LeFebvre, J. C.; Zhou, Y. W.; Dynes, R. C.; Cybart, S. A. (Appl. Phys. Lett., 2018)

(untitled) - Wang, J.; Li, H.; Cho, E. Y.; LeFebvere, J. C.; Cybart, S. A. (IEEE Trans. Appl. Supercond., 2019)

(untitled) - Li, H.; Cho, E. Y.; Cai, H.; Wang, Y.-T.; McCoy, S. J.; Cybart, S. A. (IEEE Trans. Appl. Supercond., 2019)

(untitled) - Müller, B.; Karrer, M.; Limberger, F.; Becker, M.; Schröppel, B.; Burkhardt, C. J.; Kleiner, R.; Goldobin, E.; Koelle, D. (Phys. Rev. Appl., 2019)

(untitled) - Li, H.; Cai, H.; Cho, E. Y.; McCoy, S. J.; Wang, Y.-T.; LeFebvre, J. C.; Zhou, Y. W.; Cybart, S. A. (Appl. Phys. Lett., 2020)

(untitled) - Cortez, A. T.; Cho, E. Y.; Li, H.; Cunnane, D.; Karasik, B.; Cybart, S. A. (IEEE Trans. Appl. Supercond., 2019)

(untitled) - Couëdo, F.; Amari, P.; Feuillet-Palma, C.; Ulysse, C.; Srivastava, Y. K.; Singh, R.; Bergeal, N.; Lesueur, J. (Sci. Rep., 2020)

(untitled) - Gozar, A.; Litombe, N. E.; Hoffman, J. E.; Božović, I. (Nano Lett., 2017)

(untitled) - Kasaei, L.; Melbourne, T.; Manichev, V.; Feldman, L. C.; Gustafsson, T.; Chen, K.; Xi, X. X.; Davidson, B. A. (AIP Adv., 2018)

(untitled) - Franken, J. H.; Hoeijmakers, M.; Lavrijsen, R.; Kohlhepp, J. T.; Swagten, H. J. M.; Koopmans, B.; van Veldhoven, E.; Maas, D. J. (J. Appl. Phys., 2011)

(untitled) - Sapozhnikov, M. V.; Vdovichev, S. N.; Ermolaeva, O. L.; Gusev, N. S.; Fraerman, A. A.; Gusev, S. A.; Petrov, Y. V. (Appl. Phys. Lett., 2016)

(untitled) - Deinhart, V.; Kern, L.-M.; Kirchhof, J. N.; Juergensen, S.; Sturm, J.; Krauss, E.; Feichtner, T.; Kovalchuk, S.; Schneider, M.; Engel, D.; Pfau, B.; Hecht, B.; et al. (Beilstein J. Nanotechnol., 2021)

(untitled) - Cress, C. D.; Wickramaratne, D.; Rosenberger, M. R.; Hennighausen, Z.; Callahan, P. G.; LaGasse, S. W.; Bernstein, N.; van ’t Erve, O. M.; Jonker, B. T.; Qadri, S. B.; Prestigiacomo, J. C.; Currie, M.; et al. (ACS Appl. Mater. Interfaces, 2021)

(untitled) - Huckfeldt, H.; Gaul, A.; David Müglich, N.; Holzinger, D.; Nissen, D.; Albrecht, M.; Emmrich, D.; Beyer, A.; Gölzhäuser, A.; Ehresmann, A. (J. Phys.: Condens. Matter, 2017)

(untitled) - Dunne, P.; Fowley, C.; Hlawacek, G.; Kurian, J.; Atcheson, G.; Colis, S.; Teichert, N.; Kundys, B.; Venkatesan, M.; Lindner, J.; Deac, A. M.; Hermans, T. M.; et al. (Nano Lett., 2020)

(untitled) - Röder, F.; Hlawacek, G.; Wintz, S.; Hübner, R.; Bischoff, L.; Lichte, H.; Potzger, K.; Lindner, J.; Fassbender, J.; Bali, R. (Sci. Rep., 2015)

(untitled) - Seol, D.; Kim, S.; Jang, W.-S.; Jin, Y.; Kang, S.; Kim, S.; Won, D.; Lee, C.; Kim, Y.-M.; Lee, J.; Yang, H.; Jeong, M. S.; et al. (Nano Energy, 2021)

(untitled) - Belianinov, A.; Iberi, V.; Tselev, A.; Susner, M. A.; McGuire, M. A.; Joy, D.; Jesse, S.; Rondinone, A. J.; Kalinin, S. V.; Ovchinnikova, O. S. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Huang, Z.; Li, W.-D.; Santori, C.; Acosta, V. M.; Faraon, A.; Ishikawa, T.; Wu, W.; Winston, D.; Williams, R. S.; Beausoleil, R. G. (Appl. Phys. Lett., 2013)

(untitled) - McCloskey, D.; Fox, D.; O'Hara, N.; Usov, V.; Scanlan, D.; McEvoy, N.; Duesberg, G. S.; Cross, G. L. W.; Zhang, H. Z.; Donegan, J. F. (Appl. Phys. Lett., 2014)

(untitled) - Sawafta, F.; Clancy, B.; Carlsen, A. T.; Huber, M.; Hall, A. R. (Nanoscale, 2014)

(untitled) - Kapitonov, Y. V.; Shapochkin, P. Y.; Beliaev, L. Y.; Petrov, Y. V.; Efimov, Y. P.; Eliseev, S. A.; Lovtcius, V. A.; Petrov, V. V.; Ovsyankin, V. V. (Opt. Lett., 2016)

(untitled) - Jiang, X.; Cai, W.; Luo, W.; Xiang, Y.; Zhang, N.; Ren, M.; Zhang, X.; Xu, J. (Nanotechnology, 2018)

(untitled) - Maguire, P.; Downing, C.; Jadwiszczak, J.; O’Brien, M.; Keane, D.; McManus, J. B.; Duesberg, G. S.; Nicolosi, V.; McEvoy, N.; Zhang, H. (J. Appl. Phys., 2019)

(untitled) - Petrov, Y. V.; Sharov, T. V.; Baraban, A. P.; Vyvenko, O. F. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2015)

(untitled) - Petrov, Y. V.; Ubyivovk, E. V.; Baraban, A. P. (AIP Conf. Proc., 2019)

(untitled) - Petrov, Y. V.; Grigoryev, E. A.; Sharov, T. V.; Baraban, A. P. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2018)

(untitled) - Petrov, Y. V.; Grigoryev, E. A.; Baraban, A. P. (Nanotechnology, 2020)

(untitled) - Maguire, P.; Jadwiszczak, J.; O’Brien, M.; Keane, D.; Duesberg, G. S.; McEvoy, N.; Zhang, H. (J. Appl. Phys., 2019)

(untitled) - Mitterreiter, E.; Liang, Y.; Golibrzuch, M.; McLaughlin, D.; Csoklich, C.; Bartl, J. D.; Holleitner, A.; Wurstbauer, U.; Bandarenka, A. S. (npj 2D Mater. Appl., 2019)

(untitled) - Zhao, Y.; Liu, D.; Chen, J.; Zhu, L.; Belianinov, A.; Ovchinnikova, O. S.; Unocic, R. R.; Burch, M. J.; Kim, S.; Hao, H.; Pickard, D. S.; Li, B.; et al. (Nat. Commun., 2017)

(untitled) - Jin, L.; Zeltmann, S. E.; Choe, H. S.; Liu, H.; Allen, F. I.; Minor, A. M.; Wu, J. (Phys. Rev. B, 2020)

(untitled) - Choe, H. S.; Li, J.; Zheng, W.; Lee, J.; Suh, J.; Allen, F. I.; Liu, H.; Choi, H.-J.; Walukiewicz, W.; Zheng, H.; Wu, J. (Appl. Phys. Lett., 2019)

(untitled) - Eswara, S.; Audinot, J.-N.; El Adib, B.; Guennou, M.; Wirtz, T.; Philipp, P. (Beilstein J. Nanotechnol., 2018)

(untitled) - Toulouse, C.; Fischer, J.; Farokhipoor, S.; Yedra, L.; Carlà, F.; Jarnac, A.; Elkaim, E.; Fertey, P.; Audinot, J.-N.; Wirtz, T.; Noheda, B.; Garcia, V.; et al. (Phys. Rev. Mater., 2021)

(untitled) - Tan, S.; Klein, K.; Shima, D.; Livengood, R.; Mutunga, E.; Vladár, A. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2014)

(untitled) - Li, R.; Zhu, R.; Chen, S.; He, C.; Li, M.; Zhang, J.; Gao, P.; Liao, Z.; Xu, J. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2019)

(untitled) - Veligura, V.; Hlawacek, G.; Berkelaar, R. P.; van Gastel, R.; Zandvliet, H. J. W.; Poelsema, B. (Beilstein J. Nanotechnol., 2013)

(untitled) - Wang, Z.-J.; Allen, F. I.; Shan, Z.-W.; Hosemann, P. (Acta Mater., 2016)

(untitled) - Liu, W.; Cheng, L.; Li, X.; Wang, Y. (Nanoscale, 2016)

(untitled) - Jiang, W.; Zhang, J.; Edwards, D. J.; Overman, N. R.; Zhu, Z.; Price, L.; Gigax, J.; Castanon, E.; Shao, L.; Senor, D. J. (J. Nucl. Mater., 2017)

(untitled) - Frazer, D.; Szornel, J.; Krumwiede, D. L.; Terrani, K. A.; Hosemann, P. (Exp. Mech., 2017)

(untitled) - Bergner, F.; Hlawacek, G.; Heintze, C. (J. Nucl. Mater., 2018)

(untitled) - Chen, Z.; Niu, L.-L.; Wang, Z.; Tian, L.; Kecskes, L.; Zhu, K.; Wei, Q. (Acta Mater., 2018)

(untitled) - Allen, F. I.; Hosemann, P.; Balooch, M. (Scr. Mater., 2020)

(untitled) - Xiao, S.; Ma, Y.; Tian, L.; Li, M.; Qi, C.; Wang, B. (Nucl. Mater. Energy, 2020)

(untitled) - Shan, G. B.; Chen, Y. Z.; Liang, N. N.; Dong, H.; Zhang, W. X.; Suo, T.; Liu, F. (Mater. Lett., 2019)

(untitled) - Mairov, A.; Frazer, D.; Hosemann, P.; Sridharan, K. (Scr. Mater., 2019)

(untitled) - Jiang, W.; Sundararajan, J. A.; Varga, T.; Bowden, M. E.; Qiang, Y.; McCloy, J. S.; Henager, C. H., Jr; Montgomery, R. O. (Adv. Funct. Mater., 2014)

(untitled) - Wang, Y.-C.; Tian, L.; Liu, F.; Qin, Y.-B.; Zheng, G.; Wang, J.-T.; Ma, E.; Shan, Z.-W. (Small, 2017)

(untitled) - Chen, M.; Best, J. P.; Shorubalko, I.; Michler, J.; Spolenak, R.; Wheeler, J. M. (Carbon, 2020)

(untitled) - Rzeznik, L.; Fleming, Y.; Wirtz, T.; Philipp, P. (Beilstein J. Nanotechnol., 2016)

(untitled) - Tavares, L.; Chiriaev, S.; Adashkevich, V.; Taboryski, R.; Rubahn, H.-G. (Nanotechnology, 2020)

(untitled) - Allen, F. I.; Velez, N. R.; Thayer, R. C.; Patel, N. H.; Jones, M. A.; Meyers, G. F.; Minor, A. M. (Nanoscale, 2019)

(untitled) - Zhang, L.; Heinig, N. F.; Bazargan, S.; Abd-Ellah, M.; Moghimi, N.; Leung, K. T. (Nanotechnology, 2015)

(untitled) - Kim, C.-S.; Hobbs, R. G.; Agarwal, A.; Yang, Y.; Manfrinato, V. R.; Short, M. P.; Li, J.; Berggren, K. K. (Nanotechnology, 2020)

(untitled) - Aramesh, M.; Mayamei, Y.; Wolff, A.; Ostrikov, K. K. (Nat. Commun., 2018)

(untitled) - Aramesh, M. (Phys. Status Solidi RRL, 2018)

(untitled) - Xu, X.; Prüfer, T.; Wolf, D.; Engelmann, H.-J.; Bischoff, L.; Hübner, R.; Heinig, K.-H.; Möller, W.; Facsko, S.; von Borany, J.; Hlawacek, G. (Beilstein J. Nanotechnol., 2018)

(untitled) - Arora, W. J.; Sijbrandij, S.; Stern, L.; Notte, J.; Smith, H. I.; Barbastathis, G. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2007)

(untitled) - Gonzalez, C. M.; Timilsina, R.; Li, G.; Duscher, G.; Rack, P. D.; Slingenbergh, W.; van Dorp, W. F.; De Hosson, J. T. M.; Klein, K. L.; Wu, H. M.; Stern, L. A. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2014)

(untitled) - Liu, Z.; Du, H.; Li, J.; Lu, L.; Li, Z.-Y.; Fang, N. X. (Sci. Adv., 2018)

(untitled) - Zhang, C.; Dyck, O.; Garfinkel, D. A.; Stanford, M. G.; Belianinov, A. A.; Fowlkes, J. D.; Jesse, S.; Rack, P. D. (Nanomaterials, 2019)

(untitled) - Prewett, P. D.; Hagen, C. W.; Lenk, C.; Lenk, S.; Kaestner, M.; Ivanov, T.; Ahmad, A.; Rangelow, I. W.; Shi, X.; Boden, S. A.; Robinson, A. P. G.; Yang, D.; et al. (Beilstein J. Nanotechnol., 2018)

Frontiers of Nanoscience - Shi, X.; Boden, S. A. (Chapter 17 - Scanning helium ion beam lithography, 2016)

Helium Ion Microscopy - Kalhor, N.; Alkemade, P. F. A. (Resist Assisted Patterning, 2016)

(untitled) - Sidorkin, V.; van Veldhoven, E.; van der Drift, E.; Alkemade, P.; Salemink, H.; Maas, D. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2009)

(untitled) - Winston, D.; Cord, B. M.; Ming, B.; Bell, D. C.; DiNatale, W. F.; Stern, L. A.; Vladar, A. E.; Postek, M. T.; Mondol, M. K.; Yang, J. K. W.; Berggren, K. K. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2009)

(untitled) - Cai, J.; Zhu, Z.; Alkemade, P. F. A.; van Veldhoven, E.; Wang, Q.; Ge, H.; Rodrigues, S. P.; Cai, W.; Li, W.-D. (Adv. Mater. (Weinheim, Ger.), 2018)

(untitled) - Flatabø, R.; Agarwal, A.; Hobbs, R.; Greve, M. M.; Holst, B.; Berggren, K. K. (Nanotechnology, 2018)

(untitled) - Lee, C.-L.; Chien, S.-W.; Tsai, K.-Y. (Proc. SPIE, 2018)

(untitled) - Zhang, L.; Thomas, J. P.; Guan, X.; Heinig, N. F.; Leung, K. T. (Nanotechnology, 2020)

(untitled) - Zhang, X.; Vieker, H.; Beyer, A.; Gölzhäuser, A. (Beilstein J. Nanotechnol., 2014)

(untitled) - Winston, D.; Manfrinato, V. R.; Nicaise, S. M.; Cheong, L. L.; Duan, H.; Ferranti, D.; Marshman, J.; McVey, S.; Stern, L.; Notte, J.; Berggren, K. K. (Nano Lett., 2011)

(untitled) - Alkemade, P.; Sidorkin, V.; Chen, P.; van der Drift, E.; van Langen, A.; Maas, D.; van Velhoven, E.; Scipioni, L. (Microsc. Anal., 2010)

Nanofabrication: Techniques and Principles - van der Drift, E.; Maas, D. J. (Helium Ion Lithography, 2012)

(untitled) - Fallica, R.; Kirchner, R.; Ekinci, Y.; Mailly, D. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2016)

Advances in Patterning Materials and Processes XXXIII - Luo, F.; Manichev, V.; Li, M.; Mitchson, G.; Yakshinskiy, B.; Gustafsson, T.; Johnson, D.; Garfunkel, E. (Helium ion beam lithography (HIBL) using HafSOx as the resist, 2016)

Extreme Ultraviolet (EUV) Lithography V - Maas, D.; van Veldhoven, E.; van Langen-Suurling, A.; Alkemade, P. F. A.; Wuister, S.; Hoefnagels, R.; Verspaget, C.; Meessen, J.; Fliervoet, T. (Evaluation of EUV resist performance below 20nm CD using helium ion lithography, 2014)

Advances in Patterning Materials and Processes XXXII - Kalhor, N.; Mulckhuyse, W.; Alkemade, P.; Maas, D. (Impact of pixel-dose optimization on pattern fidelity for helium ion beam lithography on EUV resist, 2015)

Advances in Patterning Materials and Processes XXXV - Li, M.; Manichev, V.; Yu, F.; Hutchison, D.; Nyman, M.; Gustafsson, T.; Feldman, L. C.; Garfunkel, E. L. (Novel Sn-based photoresist for high aspect ratio patterning, 2018)

(untitled) - Shi, X.; Prewett, P.; Huq, E.; Bagnall, D. M.; Robinson, A. P. G.; Boden, S. A. (Microelectron. Eng., 2016)

(untitled) - Hartl, H.; East, C.; Xu, Y.; Yambem, S. D.; Fairfull-Smith, K. E.; MacLeod, J. (Nanotechnology, 2019)

(untitled) - Reddy, P. G.; Thakur, N.; Lee, C.-L.; Chien, S.-W.; Pradeep, C. P.; Ghosh, S.; Tsai, K.-Y.; Gonsalves, K. E. (AIP Adv., 2017)

Novel Patterning Technologies 2018 - Sharma, S. K.; Reddy, P. G.; Moinuddin, M. G.; Ghosh, S.; Pradeep, C. P.; Gonsalves, K. E. (Helium ion active hybrid non-chemically amplified resist (n-CAR) for sub-10 nm patterning applications, 2018)

(untitled) - Cattoni, A.; Mailly, D.; Dalstein, O.; Faustini, M.; Seniutinas, G.; Rösner, B.; David, C. (Microelectron. Eng., 2018)

(untitled) - Lewis, S. M.; Hunt, M. S.; DeRose, G. A.; Alty, H. R.; Li, J.; Wertheim, A.; De Rose, L.; Timco, G. A.; Scherer, A.; Yeates, S. G.; Winpenny, R. E. P. (Nano Lett., 2019)

(untitled) - Kumar, R.; Chauhan, M.; Moinuddin, M. G.; Sharma, S. K.; Gonsalves, K. E. (ACS Appl. Mater. Interfaces, 2020)

Advances in Patterning Materials and Processes XXXVII - Sharma, S. K.; Kumar, R.; Chauhan, M.; Moinuddin, M. G.; Peter, J.; Ghosh, S.; Pradeep, C. P.; Gonsalves, K. E. (All-new nickel-based Metal Core Organic Cluster (MCOC) resist for N7+ node patterning, 2020)

Advances in Patterning Materials and Processes XXXVII - Sharma, S. K.; Moinuddin, M. G.; Yogesh, M.; Sharma, S.; Sahani, M.; Ghosh, S.; Gonsalves, K. E. (Focusing on nanoparticles-based photomultiplier in n-CARs, 2020)

(untitled) - Li, W.-D.; Wu, W.; Stanley Williams, R. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2012)

Graphene Nano-Ribbon Patterning in the ORION® PLUS. In Carl Zeiss Application Note - Pickard, D.; Scipioni, L. (Carl Zeiss, 2009)

(untitled) - Abbas, A. N.; Liu, G.; Liu, B.; Zhang, L.; Liu, H.; Ohlberg, D.; Wu, W.; Zhou, C. (ACS Nano, 2014)

(untitled) - Kalhor, N.; Boden, S. A.; Mizuta, H. (Microelectron. Eng., 2014)

2011 16th International Solid-State Sensors, Actuators and Microsystems Conference - Annamalai, M.; Mathew, S.; Viswanathan, V.; Fang, C.; Pickard, D. S.; Palaniapan, M. (Design, fabrication and Helium Ion Microscope patterning of suspended nanomechanical graphene structures for NEMS applications, 2011)

(untitled) - Iberi, V.; Vlassiouk, I.; Zhang, X.-G.; Matola, B.; Linn, A.; Joy, D. C.; Rondinone, A. J. (Sci. Rep., 2015)

(untitled) - Schmidt, M. E.; Iwasaki, T.; Muruganathan, M.; Haque, M.; Van Ngoc, H.; Ogawa, S.; Mizuta, H. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Deng, Y.; Wang, G.; Qiu, Y.; He, D.; Lin, J.; He, J. (Nanotechnology, 2020)

(untitled) - Simeone, D.; Esposito, M.; Scuderi, M.; Calafiore, G.; Palermo, G.; De Luca, A.; Todisco, F.; Sanvitto, D.; Nicotra, G.; Cabrini, S.; Tasco, V.; Passaseo, A.; et al. (ACS Photonics, 2018)

(untitled) - Hahn, C.; Hajebifard, A.; Berini, P. (Nanophotonics, 2020)

(untitled) - Chen, Y.; Hu, Y.; Zhao, J.; Deng, Y.; Wang, Z.; Cheng, X.; Lei, D.; Deng, Y.; Duan, H. (Adv. Funct. Mater., 2020)

(untitled) - Seitl, L.; Laible, F.; Dickreuter, S.; Gollmer, D. A.; Kern, D. P.; Fleischer, M. (Nanotechnology, 2020)

(untitled) - Kuznetsov, A. I.; Miroshnichenko, A. E.; Hsing Fu, Y.; Viswanathan, V.; Rahmani, M.; Valuckas, V.; Ying Pan, Z.; Kivshar, Y.; Pickard, D. S.; Luk’yanchuk, B. (Nat. Commun., 2014)

(untitled) - Tan, S.; Livengood, R.; Hack, P.; Hallstein, R.; Shima, D.; Notte, J.; McVey, S. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2011)

(untitled) - Stanford, M. G.; Mahady, K.; Lewis, B. B.; Fowlkes, J. D.; Tan, S.; Livengood, R.; Magel, G. A.; Moore, T. M.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Buchheim, J.; Wyss, R. M.; Shorubalko, I.; Park, H. G. (Nanoscale, 2016)

(untitled) - Kim, S.; Dyck, O.; Ievlev, A. V.; Vlassiouk, I. V.; Kalinin, S. V.; Belianinov, A.; Jesse, S.; Ovchinnikova, O. S. (Carbon, 2018)

(untitled) - Fox, D.; Zhou, Y. B.; O’Neill, A.; Kumar, S.; Wang, J. J.; Coleman, J. N.; Duesberg, G. S.; Donegan, J. F.; Zhang, H. Z. (Nanotechnology, 2013)

(untitled) - Araujo, E. N. D.; Brant, J. C.; Archanjo, B. S.; Medeiros-Ribeiro, G.; Plentz, F.; Alves, E. S. (Phys. Rev. B, 2015)

(untitled) - Nanda, G.; Goswami, S.; Watanabe, K.; Taniguchi, T.; Alkemade, P. F. A. (Nano Lett., 2015)

(untitled) - Nanda, G.; Hlawacek, G.; Goswami, S.; Watanabe, K.; Taniguchi, T.; Alkemade, P. F. A. (Carbon, 2017)

(untitled) - Iberi, V.; Ievlev, A. V.; Vlassiouk, I.; Jesse, S.; Kalinin, S. V.; Joy, D. C.; Rondinone, A. J.; Belianinov, A.; Ovchinnikova, O. S. (Nanotechnology, 2016)

(untitled) - Gilbert, S. M.; Liu, S.; Schumm, G.; Zettl, A. (MRS Adv., 2018)

(untitled) - López, J. J.; Ambrosio, A.; Dai, S.; Huynh, C.; Bell, D. C.; Lin, X.; Rivera, N.; Huang, S.; Ma, Q.; Eyhusen, S.; Kaminer, I. E.; Watanabe, K.; et al. (Small, 2018)

(untitled) - Thiele, C.; Vieker, H.; Beyer, A.; Flavel, B. S.; Hennrich, F.; Muñoz Torres, D.; Eaton, T. R.; Mayor, M.; Kappes, M. M.; Gölzhäuser, A.; v. Löhneysen, H.; Krupke, R. (Appl. Phys. Lett., 2014)

(untitled) - Zheng, W.; Li, P.; van den Hurk, R.; Evoy, S. (Sensors, 2016)

(untitled) - Yang, J.; Ferranti, D. C.; Stern, L. A.; Sanford, C. A.; Huang, J.; Ren, Z.; Qin, L.-C.; Hall, A. R. (Nanotechnology, 2011)

(untitled) - Hall, A. R. (Microsc. Today, 2012)

(untitled) - Xia, D.; Huynh, C.; McVey, S.; Kobler, A.; Stern, L.; Yuan, Z.; Ling, X. S. (Nanoscale, 2018)

Helium Ion Microscopy - Zahid, O. K.; Hall, A. R. (Helium Ion Microscope Fabrication of Solid-State Nanopore Devices for Biomolecule Analysis, 2016)

(untitled) - Wu, H.; Chen, Y.; Zhou, Q.; Wang, R.; Xia, B.; Ma, D.; Luo, K.; Liu, Q. (Anal. Chem. (Washington, DC, U. S.), 2016)

(untitled) - Hall, A. R. (Microsc. Microanal., 2013)

(untitled) - Sawafta, F.; Carlsen, A. T.; Hall, A. R. (Sensors, 2014)

(untitled) - Carlsen, A. T.; Briggs, K.; Hall, A. R.; Tabard-Cossa, V. (Nanotechnology, 2017)

(untitled) - Emmrich, D.; Beyer, A.; Nadzeyka, A.; Bauerdick, S.; Meyer, J. C.; Kotakoski, J.; Gölzhäuser, A. (Appl. Phys. Lett., 2016)

(untitled) - Shorubalko, I.; Choi, K.; Stiefel, M.; Park, H. G. (Beilstein J. Nanotechnol., 2017)

(untitled) - Chen, D.; Qiao, R.; Xu, X.; Dong, W.; Wang, L.; Ma, R.; Liu, C.; Zhang, Z.; Wu, M.; Liu, L.; Bao, L.; Wang, H.-T.; et al. (Nanoscale, 2019)

(untitled) - Deng, Y.; Huang, Q.; Zhao, Y.; Zhou, D.; Ying, C.; Wang, D. (Nanotechnology, 2017)

(untitled) - Liu, F.; Wang, Z.; Nakanao, S.; Ogawa, S.; Morita, Y.; Schmidt, M.; Haque, M.; Muruganathan, M.; Mizuta, H. (Micromachines, 2020)

(untitled) - Wang, H.; Xie, W.; Wang, Y.; Zhu, J.; Liu, M.; Lu, W.; Deng, Y.; Wang, G.; Wang, D. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2018)

(untitled) - Yoon, K.; Rahnamoun, A.; Swett, J. L.; Iberi, V.; Cullen, D. A.; Vlassiouk, I. V.; Belianinov, A.; Jesse, S.; Sang, X.; Ovchinnikova, O. S.; Rondinone, A. J.; Unocic, R. R.; et al. (ACS Nano, 2016)

(untitled) - Maguire, P.; Fox, D. S.; Zhou, Y.; Wang, Q.; O'Brien, M.; Jadwiszczak, J.; Cullen, C. P.; McManus, J.; Bateman, S.; McEvoy, N.; Duesberg, G. S.; Zhang, H. (Phys. Rev. B, 2018)

(untitled) - Liu, J.; Jin, L.; Allen, F. I.; Gao, Y.; Ci, P.; Kang, F.; Wu, J. (Nano Lett., 2021)

(untitled) - Yang, C.-W.; Chen, W.-C.; Chou, C.; Lin, H.-H. (J. Cryst. Growth, 2017)

(untitled) - Scholder, O.; Jefimovs, K.; Shorubalko, I.; Hafner, C.; Sennhauser, U.; Bona, G.-L. (Nanotechnology, 2013)

(untitled) - Wang, Y.; Abb, M.; Boden, S. A.; Aizpurua, J.; de Groot, C. H.; Muskens, O. L. (Nano Lett., 2013)

Chemical, Biological, Radiological, Nuclear, and Explosives (CBRNE) Sensing XVI - Black, L.-J.; Wang, Y.; Abb, M.; Boden, S. A.; de Groot, C. H.; Arbouet, A.; Muskens, O. L. (New plasmonic materials and fabrication tools for near- and mid-infrared sensing and spectroscopy, 2015)

(untitled) - Kollmann, H.; Piao, X.; Esmann, M.; Becker, S. F.; Hou, D.; Huynh, C.; Kautschor, L.-O.; Bösker, G.; Vieker, H.; Beyer, A.; Gölzhäuser, A.; Park, N.; et al. (Nano Lett., 2014)

(untitled) - Melli, M.; Polyakov, A.; Gargas, D.; Huynh, C.; Scipioni, L.; Bao, W.; Ogletree, D. F.; Schuck, P. J.; Cabrini, S.; Weber-Bargioni, A. (Nano Lett., 2013)

(untitled) - Zhang, C.; Li, J.; Belianinov, A.; Ma, Z.; Renshaw, C. K.; Gelfand, R. M. (Nanotechnology, 2020)

(untitled) - Gittinger, M.; Höflich, K.; Smirnov, V.; Kollmann, H.; Lienau, C.; Silies, M. (Nanophotonics, 2020)

(untitled) - Laible, F.; Dreser, C.; Kern, D. P.; Fleischer, M. (Nanotechnology, 2019)

(untitled) - Singh, K.; Panchenko, E.; Nasr, B.; Liu, A.; Wesemann, L.; Davis, T. J.; Roberts, A. (Beilstein J. Nanotechnol., 2018)

(untitled) - Semple, M.; Baladi, E.; Iyer, A. K. (IEEE J. Sel. Top. Quantum Electron., 2019)

(untitled) - Chen, K.; Razinskas, G.; Vieker, H.; Gross, H.; Wu, X.; Beyer, A.; Gölzhäuser, A.; Hecht, B. (Nanoscale, 2018)

(untitled) - Chen, Y.; Xiang, Q.; Li, Z.; Wang, Y.; Meng, Y.; Duan, H. (Nano Lett., 2016)

(untitled) - Chen, Y.; Bi, K.; Wang, Q.; Zheng, M.; Liu, Q.; Han, Y.; Yang, J.; Chang, S.; Zhang, G.; Duan, H. (ACS Nano, 2016)

(untitled) - Smirnov, V.; Stephan, S.; Westphal, M.; Emmrich, D.; Beyer, A.; Gölzhäuser, A.; Lienau, C.; Silies, M. (ACS Photonics, 2021)

(untitled) - Grant-Jacob, J. A.; Zin Oo, S.; Carpignano, F.; Boden, S. A.; Brocklesby, W. S.; Charlton, M. D. B.; Melvin, T. (Nanotechnology, 2016)

(untitled) - Oo, S. Z.; Silva, G.; Carpignano, F.; Noual, A.; Pechstedt, K.; Mateos, L.; Grant-Jacob, J. A.; Brocklesby, B.; Horak, P.; Charlton, M.; Boden, S. A.; Melvin, T. (Sens. Bio-Sens. Res., 2016)

(untitled) - Archanjo, B. S.; Vasconcelos, T. L.; Oliveira, B. S.; Song, C.; Allen, F. I.; Achete, C. A.; Ercius, P. (ACS Photonics, 2018)

(untitled) - Scipioni, L.; Ferranti, D. C.; Smentkowski, V. S.; Potyrailo, R. A. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2010)

Nanofabrication: Techniques and Principles - Alkemade, P. F. A.; van Veldhoven, E. (Deposition, Milling, and Etching with a Focused Helium Ion Beam, 2012)

Scanning Microscopies 2011: Advanced Microscopy Technologies for Defense, Homeland Security, Forensic, Life, Environmental, and Industrial Sciences - Ananth, M.; Stern, L.; Ferranti, D.; Huynh, C.; Notte, J.; Scipioni, L.; Sanford, C.; Thompson, B. (Creating nanohole arrays with the helium ion microscope, 2011)

(untitled) - Xia, D.; Zhu, X.; Khanom, F.; Runt, D. (Nanotechnology, 2020)

(untitled) - Xia, D.; Jiang, Y.-B.; Notte, J.; Runt, D. (Appl. Surf. Sci., 2021)

(untitled) - Timilsina, R.; Tan, S.; Livengood, R.; Rack, P. D. (Nanotechnology, 2014)

(untitled) - Pekin, T. C.; Allen, F. I.; Minor, A. M. J. (J. Microsc. (Oxford, U. K.), 2016)

(untitled) - El-Atwani, O.; Huynh, C.; Norris, S. (Appl. Surf. Sci., 2016)

(untitled) - Wu, H.; Ferranti, D.; Stern, L. (Microelectron. Reliab., 2014)

(untitled) - Timilsina, R.; Rack, P. D. (Nanotechnology, 2013)

(untitled) - Mahady, K.; Tan, S.; Greenzweig, Y.; Livengood, R.; Raveh, A.; Rack, P. (Nanotechnology, 2017)

(untitled) - Mahady, K. T.; Tan, S.; Greenzweig, Y.; Raveh, A.; Rack, P. D. (Nanotechnology, 2018)

(untitled) - Burnett, J.; Sagar, J.; Kennedy, O. W.; Warburton, P. A.; Fenton, J. C. (Phys. Rev. Appl., 2017)

(untitled) - Kennedy, O. W.; Burnett, J.; Fenton, J. C.; Constantino, N. G. N.; Warburton, P. A.; Morton, J. J. L.; Dupont-Ferrier, E. (Phys. Rev. Appl., 2019)

(untitled) - Potter, J. A.; Kennedy, O. W.; Fenton, J. C.; Warburton, P. A. (IEEE Trans. Appl. Supercond., 2020)

(untitled) - Hong, J.; Hadjikhani, A.; Stone, M.; Allen, F. I.; Safonov, V.; Liang, P.; Bokor, J.; Khizroev, S. (IEEE Trans. Magn., 2016)

(untitled) - Rudneva, M.; van Veldhoven, E.; Malladi, S. K.; Maas, D.; Zandbergen, H. W. (J. Mater. Res., 2013)

(untitled) - Stanford, M. G.; Lewis, B. B.; Iberi, V.; Fowlkes, J. D.; Tan, S.; Livengood, R.; Rack, P. D. (Small, 2016)

(untitled) - Stanford, M. G.; Pudasaini, P. R.; Cross, N.; Mahady, K.; Hoffman, A. N.; Mandrus, D. G.; Duscher, G.; Chisholm, M. F.; Rack, P. D. (Small Methods, 2017)

(untitled) - Mahady, K. T.; Tan, S.; Greenzweig, Y.; Raveh, A.; Rack, P. D. (Nanoscale Adv., 2019)

(untitled) - Xia, D.; McVey, S.; Huynh, C.; Kuehn, W. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Hang, S.; Moktadir, Z.; Mizuta, H. (Carbon, 2014)

(untitled) - Unocic, K. A.; Mills, M. J.; Daehn, G. S. (J. Microsc. (Oxford, U. K.), 2010)

(untitled) - Reiner, J. C.; Nellen, P.; Sennhauser, U. (Microelectron. Reliab., 2004)

(untitled) - Fox, D.; Chen, Y.; Faulkner, C. C.; Zhang, H. (Beilstein J. Nanotechnol., 2012)

(untitled) - Allen, F.; Notte, J.; Xia, D.; Blanchard, P.; Zhang, R.; Minor, A.; Sanford, N. (Microsc. Microanal., 2020)

(untitled) - Best, J. P.; Zechner, J.; Shorubalko, I.; Oboňa, J. V.; Wehrs, J.; Morstein, M.; Michler, J. (Scr. Mater., 2016)

(untitled) - Xu, X.; Heinig, K.-H.; Möller, W.; Engelmann, H.-J.; Klingner, N.; Gharbi, A.; Tiron, R.; von Borany, J.; Hlawacek, G. (Semicond. Sci. Technol., 2019)

(untitled) - Alkemade, P. F. A.; Miro, H. (Appl. Phys. A: Mater. Sci. Process., 2014)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2008)

(untitled) - Sanford, C. A.; Stern, L.; Barriss, L.; Farkas, L.; DiManna, M.; Mello, R.; Maas, D. J.; Alkemade, P. F. A. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2009)

(untitled) - Drezner, Y.; Greenzweig, Y.; Fishman, D.; van Veldhoven, E.; Maas, D. J.; Raveh, A.; Livengood, R. H. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2012)

(untitled) - Boden, S. A.; Moktadir, Z.; Bagnall, D. M.; Mizuta, H.; Rutt, H. N. (Microelectron. Eng., 2011)

(untitled) - Chen, P.; van Veldhoven, E.; Sanford, C. A.; Salemink, H. W. M.; Maas, D. J.; Smith, D. A.; Rack, P. D.; Alkemade, P. F. A. (Nanotechnology, 2010)

(untitled) - Hill, R.; Faridur Rahman, F. H. M. (Nucl. Instrum. Methods Phys. Res., Sect. A, 2011)

(untitled) - Córdoba, R.; Ibarra, A.; Mailly, D.; De Teresa, J. M. (Nano Lett., 2018)

(untitled) - Alkemade, P. F. A.; Chen, P.; van Veldhoven, E.; Maas, D. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2010)

(untitled) - Smith, D. A.; Joy, D. C.; Rack, P. D. (Nanotechnology, 2010)

(untitled) - Alkemade, P. F. A.; Miro, H.; van Veldhoven, E.; Maas, D. J.; Smith, D. A.; Rack, P. D. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2011)

Metrology, Inspection, and Process Control for Microlithography XXIV - Maas, D.; van Veldhoven, E.; Chen, P.; Sidorkin, V.; Salemink, H.; van der Drift, E.; Alkemade, P. (Nanofabrication with a helium ion microscope, 2010)

(untitled) - Hayashida, M.; Iijima, T.; Fujimoto, T.; Ogawa, S. (Micron, 2012)

(untitled) - Scipioni, L.; Sanford, C.; van Veldhoven, E.; Maas, D. (Microsc. Today, 2011)

(untitled) - Wu, H.; Stern, L. A.; Xia, D.; Ferranti, D.; Thompson, B.; Klein, K. L.; Gonzalez, C. M.; Rack, P. D. (J. Mater. Sci.: Mater. Electron., 2014)

(untitled) - Orús, P.; Córdoba, R.; Hlawacek, G.; De Teresa, J. M. (Nanotechnology, 2021)

(untitled) - Alkemade, P. F. A.; Koster, E. M.; van Veldhoven, E.; Maas, D. J. (Scanning, 2012)

(untitled) - Nanda, G.; van Veldhoven, E.; Maas, D.; Sadeghian, H.; Alkemade, P. F. A. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2015)

(untitled) - Timilsina, R.; Smith, D. A.; Rack, P. D. (Nanotechnology, 2013)

(untitled) - Kohama, K.; Iijima, T.; Hayashida, M.; Ogawa, S. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2013)

(untitled) - Wu, H. M.; Stern, L. A.; Chen, J. H.; Huth, M.; Schwalb, C. H.; Winhold, M.; Porrati, F.; Gonzalez, C. M.; Timilsina, R.; Rack, P. D. (Nanotechnology, 2013)

(untitled) - Ievlev, A. V.; Jakowski, J.; Burch, M. J.; Iberi, V.; Hysmith, H.; Joy, D. C.; Sumpter, B. G.; Belianinov, A.; Unocic, R. R.; Ovchinnikova, O. S. (Nanoscale, 2017)

(untitled) - Allen, F. I. (Micromachines, 2021)

(untitled) - Hayashida, M.; Iijima, T.; Tsukahara, M.; Ogawa, S. (Micron, 2013)

(untitled) - Córdoba, R.; Ibarra, A.; Mailly, D.; Guillamón, I.; Suderow, H.; De Teresa, J. M. (Beilstein J. Nanotechnol., 2020)

(untitled) - Córdoba, R.; Mailly, D.; Rezaev, R. O.; Smirnova, E. I.; Schmidt, O. G.; Fomin, V. M.; Zeitler, U.; Guillamón, I.; Suderow, H.; De Teresa, J. M. (Nano Lett., 2019)

(untitled) - Belianinov, A.; Burch, M. J.; Ievlev, A.; Kim, S.; Stanford, M. G.; Mahady, K.; Lewis, B. B.; Fowlkes, J. D.; Rack, P. D.; Ovchinnikova, O. S. (Micromachines, 2020)

2013 IEEE International Interconnect Technology Conference - IITC - Kohama, K.; Iijima, T.; Hayashida, M.; Ogawa, S. (Beam-substrate interaction during tungsten deposition by helium ion microscope, 2013)

(untitled) - Yang, P.-S.; Huang, Z.-d.; Huang, K.-W.; Chen, M.-J. (Ultramicroscopy, 2020)

(untitled) - Onishi, K.; Guo, H.; Nagano, S.; Fujita, D. (Microscopy (Oxford, U. K.), 2014)

(untitled) - Basset, J.; Watfa, D.; Aiello, G.; Féchant, M.; Morvan, A.; Estève, J.; Gabelli, J.; Aprili, M.; Weil, R.; Kasumov, A.; Bouchiat, H.; Deblock, R. (Appl. Phys. Lett., 2019)